Development, Characterisation, and Performance Evaluation of Some Indigenous Plants for Faecal Sludge Treatment in Ghana - Issahaku Ahmed; Esi Awuah; Helen M. K. Essandoh; Sampson Oduro-Kwarteng; Dennis Ofori-Amanfo; Florence Cobbold; Joshua Oduro-Adu (International Journal of Polymer Science, 2023)
The search for alternative solutions for sustainable management of faecal sludge in the area of dewatering with biocoagulants/bioflocculants remains unfulfilled. Some available and accessible indigenous plants in the northern part of Ghana have been characterised and subsequently evaluated in their suitability for use as biocoagulant/bioflocculants. The Yila (Crossopteryx febrifuga) and the Voulo (Grewia mollis) plants were the indigenous plants used in this study. Three applications from the Yila wooden stem, the Yila bark, and the Voulo at different treatment concentrations with faecal sludge were monitored. The Yila wooden stem gave a potential of pollutant removal up to about 83.99%, 93.79%, and 91.54% for Chemical Oxygen Demand (COD), Total Suspended Solids (TSS), and turbidity, respectively. Application of the Yila bark gave a respective removal efficiency of up to about 77.39%, 82.02%, and 54.60% for COD, TSS, and turbidity. The efficiency of the Voulo plant obtained for COD, TSS, and turbidity was up to about 80.43%, 86.83%, and 72.55%, respectively. No cyanogenic or toxic compounds were identified in the characterised raw materials used for this study. The study has revealed the potential of producing biocoagulants that can perform as effectively as synthetic/chemical coagulants using locally natural raw materials but the use of it at large scale will only be applicable for batch or semi-batch systems. Some interesting constituents identified in the plants under consideration, such as trialkyl bismuthine and furan derivative, can open up opportunities to elucidate the potential applications of these identified plants in the areas of pharmaceuticals, cosmetics, glass and ceramics, rubber production, and other applicable medicinal advantageous areas.